1964
DOI: 10.1177/000348946407300424
|View full text |Cite
|
Sign up to set email alerts
|

XCIV A Study of the Management of Caustic Esophageal Trauma

Abstract: The comphcations of caustic esophageal trauma are: death, esophageal stricture, perforation, major surgery, and hfelong disabil ity. Reviews have shown that, in the past, stricture could be expected in from 40 to 80 per cent of those with esophageal burns.** Today, with modern therapy, the stricture rate can be reduced to from 3 to 5 per cent.* The purpose of this paper is to describe a form of treat ment which is effective to this end.Over a two year period, seventy patients were admitted to the University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In the presented material 76 per cent of the lye corrosions were the consequence of a suicidal attempt ._Lye had in most cases been ingested in olid form and in a large amount, accordingly most of the corrosions were very severe and of the 'full-thickness type' (Yarington et al, 1964). The effect of the swallowed lye is usually exerted on the lips, tongue and pharynx as well as on the oesophagus.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the presented material 76 per cent of the lye corrosions were the consequence of a suicidal attempt ._Lye had in most cases been ingested in olid form and in a large amount, accordingly most of the corrosions were very severe and of the 'full-thickness type' (Yarington et al, 1964). The effect of the swallowed lye is usually exerted on the lips, tongue and pharynx as well as on the oesophagus.…”
Section: Discussionmentioning
confidence: 88%
“…The effect of the swallowed lye is usually exerted on the lips, tongue and pharynx as well as on the oesophagus. Oesophageal corrosions may, however, occur without oropharyngeal burns; this was the case in more than 15 per cent of the patients reported by Yarington et al (1964). On the other hand a considerable number of patients who have ingested a corrosive have no lesions in the oesophagus, although the mouth and pharynx are involved; this was the case in 44 per cent in a series reported by Palva (i960) and in 25 per cent in the series reported by Yarington et al (1964).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Compulsive hot bathing had a serious impact in almost half of these patients. Several patient received a psychiatric diagnosis for the abnormal behavior (7) or along the extenuating course of the condition (13). Despite the large number of treatment used, the only definitive therapy appeared to be cannabis use cessation.…”
Section: Populations Facing Chemical Weapons In the Middle-east The mentioning
confidence: 99%
“…Hyperchloremic metabolic acidosis and hypernatriemia has been described in four adult deliberate ingestion and seem related with high-grade gastricesophageal lesions and poor prognosis (1 fatal case with gastric perforation, 1 gastric perforation, 1 esophageal perforation and 1 with esophageal lesions and hemodynamic disorders) 8,[10][11][12] . Concerning accidental exposure, about 40% of adult patient that ingested 1-2 swallows of 5-10% hypochlorite solution presented moderate gastric-esophageal lesions 13,14 . Pediatric case series showed that one accidental swallow of 4-10% hypochlorite at 10-11 pH solution may be associated with moderate gastric (5% of patients) or esophageal lesions (30% of patients) 15,16 .…”
mentioning
confidence: 99%